PENGGUNAAN MODEL PROBLEM BASED LEARNING DENGAN MULTIREPRESENTASI PADA USAHA DAN ENERGI DI SMA - F03109028, Fitri Arifiyanti; Djudin, Tomo; TMS, Haratua (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2013)
Abstract: The purpose of this research is to know the effectiveness of implementation problem based learning model with multiple representations in reduce the percentage of students difficulty in XI IPA SMAN 1 Pontianak. The research design is one group pretest-posttest design, and the instrument uses essay test . Test reliability (0, 5) is classified as medium and test validity (3,56) is classified as medium. The effect size of this research (2,18) is classified high but the reduction percentage of the students difficulty (41,33%) is classified as medium. The percentage increase of the students skill in multirepresentation (52,38%) is classified as medium. The research doesnt find significant correlation between the posttest result of students difficulty and the posttest result of students skill in multirepresentation (C = 0,935, p = 0.348). The research result is suggested in the development of implementation problem based learning model with multiple representations approach. Keywords: Implementation, Problem Based Learning, Multiple representations Abstrak: Penelitian ini bertujuan untuk mengetahui mengetahui efektivitas penggunaan model problem based learning (PBL) dengan pendekatan multirepresentasi dalam menurunkan persentase kesulitan siswa kelas XI IPA SMAN 1 Pontianak. Rancangan penelitian berupa one group pretest-posttest design dan instrumen penelitian menggunakan tes essay. Reliabilitas tes (0,5) tergolong cukup dan validitas tes (3,56) tergolong sedang. Menurut aturan ruas jari harga effect size (2,18) tergolong tinggi sedangkan penurunan rata-rata persentase kesulitan siswa (41,59%) tergolong sedang. Peningkatan rata-rata persentase kemampuan multirepresentasi siswa sebesar (52,38%). Penelitian ini, tidak menemukan korelasi yang signifikan antara hasil posttest kesulitan siswa dan hasil posttest kemampuan multirepresentasi (C = 0,935, p = 0.348). Hasil penelitian ini diharapkan dapat berimplikasi pada pengembangan penggunaan model problem based learning (PBL) dengan pendekatan multirepresentasi. Kata kunci: Penggunaan, Problem Based Learning, Multirepresentasi